Influencia de la "cuota de riego" en la cantidad de agua almacenada en el suelo - Nijensohn, León (1960)
The influence of the depth of water applied in the water storage capacity. It is shown that Field Capacity after irrigation is not reached when the depth of water applied is calculated after the method of “exact refilling" (field capacity minus the moisture content before irrigation). To obtain a full available water storage it is necessary to apply an extra depth of water, that in the reported soil and for a 0.40 m. soil layer was 25% more than the calculated volume. It is pointed out the lack of a net zone of separation between the wet and the dry layers and it is deducted the possibility of advance of the wet front at water stresses higher than that corresponding to the Field Capacity. It is discussed the importance of the conclusions obtained in connection with: 1º the irrigation technique in zones of ample time periods between irrigations; 2º irrigation trials, when these are intended for obtaining moisture values of field capacity after each water application. The uneven depth of water distribution, even in layers of homogeneous texture an the possibility of influence of the different water free energies in the soil upon the activity of the root system, is pointed out.